(untitled) (Research, Society and Development, 2021)
Dengue is considered the most important acute febrile arbovirus in the world due to its burden on morbidity and mortality of countries. Cohort studies are appropriate for understanding dengue transmission dynamics and establishing baselines prior to the adoption of new control strategies. However, these studies pose major operational challenges that tend to hinder their execution, especially in developing countries. The strategies used in implanting and conducting a cohort in Central Brazil (city of Goiania) are presented, including the approaches adopted to overcome the challenges observed. The following steps are described and discussed: defining the field work team, establishing partnerships and the recruitment of participants; the initial serosurvey; technology in field research; and monitoring and evaluation of febrile episodes. A partnership between academia and public health services was the adopted approach and participation of the Municipal Health Secretariat and the Family Health Teams was essential for the proper implementation and conduction of the study. In return, the researchers’ performance favored the Health Service through surveillance and health care activities of the population. This interinstitutional experience was successful with benefits for both institutions.